Gut microbiome structure and metabolic activity in inflammatory bowel disease - Franzosa, Eric A.; Sirota-Madi, Alexandra; Avila-Pacheco, Julian; Fornelos, Nadine; Haiser, Henry J.; Reinker, Stefan; Vatanen, Tommi; Hall, A. Brantley; Mallick, Himel; McIver, Lauren J.; Sauk, Jenny S.; Wilson, Robin G.; et al. (Nature microbiology, 2019)
The inflammatory bowel diseases (IBDs), which include Crohn’s disease (CD) and ulcerative colitis (UC), are multifactorial chronic conditions of the gastrointestinal tract. While IBD has been associated with dramatic changes in the gut microbiota, changes in the gut metabolome—the molecular interface between host and microbiota—are less well understood. To address this gap, we performed untargeted metabolomic and shotgun metagenomic profiling of cross-sectional stool samples from discovery ( n = 155) and validation ( n = 65) cohorts of CD, UC and non-IBD control patients. Metabolomic and metagenomic profiles were broadly correlated with faecal calprotectin levels (a measure of gut inflammation). Across >8,000 measured metabolite features, we identified chemicals and chemical classes that were differentially abundant in IBD, including enrichments for sphingolipids and bile acids, and depletions for triacylglycerols and tetrapyrroles. While > 50% of differentially abundant metabolite features were uncharacterized, many could be assigned putative roles through metabolomic ‘guilt by association’ (covariation with known metabolites). Differentially abundant species and functions from the metagenomic profiles reflected adaptation to oxidative stress in the IBD gut, and were individually consistent with previous findings. Integrating these data, however, we identified 122 robust associations between differentially abundant species and well-characterized differentially abundant metabolites, indicating possible mechanistic relationships that are perturbed in IBD. Finally, we found that metabolome- and metagenome-based classifiers of IBD status were highly accurate and, like the vast majority of individual trends, generalized well to the independent validation cohort. Our findings thus provide an improved understanding of perturbations of the microbiome–metabolome interface in IBD, including identification of many potential diagnostic and therapeutic targets. Using metabolomics and shotgun metagenomics on stool samples from individuals with and without inflammatory bowel disease, metabolites, microbial species and genes associated with disease were identified and validated in an independent cohort.